Diagnostic study of a Bay of Bengal monsoon depression, July 1979 (MAUSAM, 1987)
Upper winds from the depression field especially in the formation stage are the major constraints, for studying their detailed structure at this stage.Monsoon Experiment (MONEX) in 1979 has provided, adequate upper air data from a depression field which formed in the north Bay of Bengal on 7 July 1979. Based on these observations, certain features like thermal structure, distribution of vorticities, divergence, radial and tangential wind, vertical wind shear inflow and out flow and vertical velocities associated with the depression have been computed and the results presented in this paper."Genesis Parameter" designed by Gray (1978) for the development of the storm based on the product of coriolis parameter, vorticity parameter, vertical wind shear parameter, ocean energy parameter, stability parameter and relative humidity parameter have been computed. In the present case, the above genesis parameter is computed to be 46 x 10-8 car K sec-1 cm-3 which is more than the average non-developing depression (26 x 10-8 calo K sec-l cm-3) and less than the developing depression (55 x 10-8 calo K sec-l cm-3) in the Atlantic.